2014
DOI: 10.1002/zoo.21120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the conservation impact of an innovative zoo‐based educational campaign: ‘Don't Palm Us Off’ for orang‐utan conservation

Abstract: With significant biodiversity loss occurring presently, increased emphasis is being placed upon the capacity of zoos to contribute to species conservation. This paper evaluates an innovative conservation education campaign ‘Don't Palm Us Off’ implemented at Melbourne Zoo, Australia. This sought to address a lack of public awareness regarding palm oil (the product most threatening the survival of the orang-utan) and to create public support for mandatory labeling of palm oil on food products, allowing for infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 40 publications
0
53
1
Order By: Relevance
“…The connection between behavioral knowledge, self-efficacy, and behavioral intent is important for further research to investigate, particularly incorporating measures of actual behavior. Some previous applied research has demonstrated that targeted campaigns at zoos were able to create behavior change, for example reducing consumption of palm oil (Pearson et al 2014) and encouraging people to keep domestic cats indoors to protect native wildlife (MacDonald 2015). Zoos should take seriously their potential for persuasion and consider more efforts to promote specific behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…The connection between behavioral knowledge, self-efficacy, and behavioral intent is important for further research to investigate, particularly incorporating measures of actual behavior. Some previous applied research has demonstrated that targeted campaigns at zoos were able to create behavior change, for example reducing consumption of palm oil (Pearson et al 2014) and encouraging people to keep domestic cats indoors to protect native wildlife (MacDonald 2015). Zoos should take seriously their potential for persuasion and consider more efforts to promote specific behavioral changes.…”
Section: Discussionmentioning
confidence: 99%
“…As a core component of the Zoo's Don't Palm Us Off campaign, the Zoopermarket is seen to have been highly successful (Pearson et al, 2014). This campaign is believed to have positively impacted manufacturers' attention to the issues of palm oil provenance and labelling, a fact which carries considerable weight for a volunteer:…”
Section: System Outcomes and Perceptionsmentioning
confidence: 96%
“…The Zoopermarket installation is a central component of the Zoos Victoria's Don't Palm Us Off campaign focusing on production of palm oil in South-East Asia and its role in loss of animal habitats (Pearson et al, 2014). Located in the visitor space at the orangutan exhibit, the installation aims to foster awareness about palm oil in consumer products, and generate consumer pressure on manufacturers to commit to improved labelling and using certified sustainable palm oil.…”
Section: Aims and Objectivesmentioning
confidence: 99%
“…Zoos and aquariums can have a significant global impact on biodiversity conservation by positively influencing the knowledge, understanding, attitudes and behaviours of the more than 700 million visitors received worldwide each year (WAZA, 2005; Barongi et al, 2015;Moss et al, 2015). A number of recent publications highlight the positive role that zoos and aquariums can play in environmental education and behaviour change, as well as demonstrating the importance of conducting well-designed monitoring and evaluation (Falk et al, 2007;Jensen, 2012;Moss et al, 2014Moss et al, , 2015Pearson et al, 2014;Barongi et al, 2015;Parsons, unpubl.). A number of recent publications highlight the positive role that zoos and aquariums can play in environmental education and behaviour change, as well as demonstrating the importance of conducting well-designed monitoring and evaluation (Falk et al, 2007;Jensen, 2012;Moss et al, 2014Moss et al, , 2015Pearson et al, 2014;Barongi et al, 2015;Parsons, unpubl.).…”
Section: Behaviour Changementioning
confidence: 99%